COMMUNITY CAPACITY BUILDING IN MAINTAINING IMMUNITY TO PREVENT RHINITIS - Bambang Aditya Nugraha, Bambang Aditya Nugraha; Gusgus Ghraha Rhamdhanie, Gusgus Ghraha Rhamdhanie; Sulastini, Sulastini (LP4M STIKes Karsa Husada Garut, 2024)
Rhinitis is one of the diseases associated with immune instability. Efforts to prevent the recurrence of rhinitis include maintaining immunity, avoiding allergies, practicing good stress management, and eating a diet that is in accordance with healthy living guidelines. Rihinits can reduce the quality of life of sufferers; therefore, it is necessary to make efforts to prevent the disease through community capacity-building activities related to rhinits. We used a virtual talk show on the Zoom meeting platform for 60 minutes as the method. Forty participants attended the activity, achieving a pretest score of 84.7 and a posttest score of 89.4. Thus, the community's capacity to increase immunity and prevent rhinitis has increased. In order to improve the health status of people with immune disorders, especially rhinitis, we expect this activity to continue in different places and with different participants